Differentially expressed, variant U1 snRNAs regulate gene expression in human cells - O'Reilly, D; Dienstbier, M; Cowley, S; Vazquez, P; Drozdz, M; Taylor, S; James, W; Murphy, S (Cold Spring Harbor Laboratory Press, 2013)
Human U1 small nuclear (sn)RNA, required for splicing of pre-mRNA, is encoded by genes on chromosome 1 (1p36). Imperfect copies of these U1 snRNA genes, also located on chromosome 1 (1q12-21), were thought to be pseudogenes. However, many of these "variant" (v)U1 snRNA genes produce fully processed transcripts. Using antisense oligonucleotides to block the activity of a specific vU1 snRNA in HeLa cells, we have identified global transcriptome changes following interrogation of the Affymetrix Human Exon ST 1.0 array. Our results indicate that this vU1 snRNA regulates expression of a subset of target genes at the level of pre-mRNA processing. This is the first indication that variant U1 snRNAs have a biological function in vivo. Furthermore, some vU1 snRNAs are packaged into unique ribonucleoproteins (RNPs), and many vU1 snRNA genes are differentially expressed in human embryonic stem cells (hESCs) and HeLa cells, suggesting developmental control of RNA processing through expression of different sets of vU1 snRNPs.